THE ADSORPTION OF WATER ON TUNGSTEN BRONZE (001) SURFACES - A STUDY BY HREELS AND PHOTOEMISSION - Aitken, D; Cox, P; Egdell, R; Hill, M; Sach, I (1983)
The adsorption of water on Na0.7WO3 (001) has been studied by HREELS and photoemission. Efficient screening of lattice vibrations by the conduction electrons leads to a low intensity of phonon losses in HREELS and enhanced sensitivity to details of surface structure as compared with non-metallic oxides. Water does not adsorb on the crystal surface at room temperature, but binds to specific surface cation sites at 150 K. This contrasts with adsorption on metal surfaces where islands of ice are found even at submonolayer coverage. © 1983.